(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze cybersecurity as a determinant of power in the contemporary international system, by demonstrating the evolution of the concept of power and its shift from a primary reliance on military and economic capabilities to a more comprehensive concept encompassing technological, informational, and cyber capabilities. The study employed a descriptive-analytical approach, reviewing and analyzing relevant international literature, studies, and reports on cybersecurity, international relations, and national power. The study concluded that cybersecurity has become a crucial element in enhancing national power, given its role in protecting critical infrastructure, information, and governmental, military, and economic systems, as well as its contribution to strengthening a state’s strategic independence. The findings also revealed that cyberspace has become an arena for international competition, and that possessing advanced cyber capabilities has become a significant factor in a state’s ability to protect its interests, exert influence, and address modern threats. Furthermore, the study demonstrated that cyber threats, such as espionage, attacks on critical infrastructure, cybercrime, and digital disinformation, pose new challenges to the stability of the international system. The study recommended integrating cybersecurity into national security strategies, developing technical and human capabilities, protecting critical infrastructure, strengthening international cooperation, and establishing more effective legal and regulatory frameworks to counter cyber threats.